Real-time sensing and low-cost experimental setup for water quantity investigation in Nature-based Solutions. Issue 2 (7th July 2022) - Gobatti, Lucas; Martins, José Rodolfo Scarati; Pereira, Maria Cristina Santana; Leite, Brenda Chaves Coelho
Abstract: Nature-based Solutions (NbS) Regulatory Ecosystem Services are less tangible and more complex to quantify. Among these, research to quantify water regulation services provided by Blue-Green Infrastructure is especially relevant for a range of different applications. However, to reach this quantification, experimentalists usually need to measure the flow rate, which can be costly if using high-end industry standard sensors. The present article brings, thus, a low-cost experimental setup for real-time data capture and logging using the US-025 ultrasonic sensor. The proposed setup measures a weir tanks' water level in order to indirectly estimate the flow rate. A successful pilot experiment is described, estimating the water quantity performance of a vegetated roof in comparison to a ceramic tiled roof. For a same event, flow rate measures taken by the proposed setup are compared to readings from a rain gauge and results show a close trend. The performance of the vegetated roof has shown substantial rainfall retention and detention when compared to the ceramic roof. It is concluded that the setup is a cost-effective tool that can be attached to inlets and outlets of different NbS for characterising a range of water flow rates capable of supporting laboratory and field data capture. HIGHLIGHTS: A low-cost flow meter was developed to combine an ultrasonic sensor and a weir. The setup was successfully used for runoff monitoring on a pilot experiment. Adherence was shown between the proposed setup results and a rain gauge. The setup can measure flow rates on inlets and outlets of Nature-based Solutions. The ultrasonic sensor speed of sound fluctuations was irrelevant within a rainfall event. Graphical Abstract